PENGARUH PENAMBAHAN RAGI TEMPE DAN EKSTRAK BROMELIN NENAS DALAM PEMBUATAN VCO (VIRGIN COCONUT OIL) - Baihaqi, Baihaqi; Hakim, Syahirman; Nuraida, Nuraida; Fridayati, Dyah (Jurnal Sains dan Teknologi Pangan, 2024)
This study aims to determine the optimum conditions of coconut milk to produce Virgin Coconut Oil (VCO) through combination of fermentation and enzymatic techniques. Technique is performed using a combination of the addition of yeast with a fixed concentration of 0.5 gram and pineapple extract (crude bromelain enzyme) with various concentration of 6 mL; 8 mL; 10 mL; 12 mL in 100 mL coconut cream, variations of pH 3 ; 4 ; 5 and the time of incubation for 24 hours at room temperature. Further analysis includes testing the quality of water content, free fatty acid content and iodine value obtained in the VCO. Results showed the treatment at pH 4; the addition of 0.5 grams of tempeh and 10 mL of pineapple extract produce optimum yield of 30.45 mL VCO. The test results of water content, free fatty acids and iodine value in a row is 0.27%; 0.144 mg KOH / g of oil; 7,12 mg iodine / 100 g oil. Virgin Coconut Oil (VCO) obtained good quality in accordance with SNI.